Propuesta pedagógica para desarrollar la competencia pragmática por medio de la aplicación de guías de aprendizaje usando los elementos esa (2019)
his article analyzes the results of a small scale research focused on developing a competence which is generally neglected in the classroom. The purpose was to work by means of the application of a pedagogical proposal which promotes a good environment that engages communicative language opportunities. The project was applied to students of seventh grade of a private institution who were not used to perform speech acts as class activities. Dialogues were performed by students in arder far students to feel confident, to maintain basic conversations. Findings reveal that if students are trained to develop oral communicative activities by using the foreign language, they improve pragmatic ability progressively.